Before (and beyond) Kant’s Paralogisms: Wolff’s Psychologia Rationalis (1734) and Mendelssohn’s Phaedon (1767) - Sales Vilalta, Guillem (Con-Textos Kantianos. International Journal of Philosophy, 2025)
This paper wants to defend two theses concerning the relationship between Kant’s critique of Rational Psychology and the contributions to this discipline made by Christian Wolff and Moses Mendelssohn, namely: (I) that Wolff’s Psychologia Rationalis (1734) does not align with Kant’s critique, not only because it seeks to explain empirical data, but more crucially because its most basic explanatory ground is itself derived from experience; (II) that Mendelssohn’s Phaedon (1767), which Kant regarded as a prime example of Rational Psychology, also fails to conform stricto sensu to Kant’s characterisation. To do so, the paper will include: (1) an introduction outlining the topic and its interest; (2) a section on Wolff’s Rational Psychology; (3) an analysis of Mendelssohn’s modulation of Wolffian Psychology; and (4) some conclusive remarks